An investigation into the study habits of distance learners: Implications for personal guidance and counselling at University of Nairobi, Kenya - Obiero, Janet; Assey, Anne; Kimamo, Charles (International Multidisciplinary Research Journal, 2020)
Quality and sustainability have been unresolved issues since the repercussion of the commercialization of distance education. Personal guidance, counseling and study habits, which are critical in maintaining the quality of distance education, have been underrated in most distance education. The study investigated the influence of personal guidance and counseling on study habits of distance learners in Bachelor of Education at the University of Nairobi. 319 respondents participated in the study by filling in questionnaires. The results of the Pearson Correlation Coefficient showed a positive correlation R= 0637 between personal guidance and counseling and study habits. The hypothesis was tested at α=.05 level of significance and the results H01: Personal guidance and counseling do not significantly influence study habits of distance learners was rejected since P=0.000<0.05. Therefore, the study concluded that there is a significant influence of personal guidance and counseling support services on the study habits of distance learners in Bachelor of Education studies of the University of Nairobi. The study recommends a paradigm shift through face to face and digital technology in the provision of personal guidance and counseling for study habits to maintain the quality of distance education.